Reinterpreting Feminism in Ideology and Practice - Adelia Rachman (Pusat Studi Gender Universitas Jember, 2023)
Feminism is widely developed in ideology and practice. A movement that elicits a great deal of individual and collective sympathy in order to fight for women’s rights, despite it continues to intersect with the subjectivity of various experiences of women’s oppression. The dynamic movement of this group, as well as the rights advocated for, contribute to the perception that feminism has gone too far. Literature studies was conducted to comprehend a tie-in the fragmentation of feminist groups to the emergence of this perception, which in turn influences rousing an anti-feminism perspective. Feminism supposed to be at the middle ground which prioritizes gender equality and justice, reduce gender bias, and base its ideology and activities on gender neutrality to address women's issues more objectively.